Analisis Implementasi Keadilan Kompensasi di PT. Jasa Raharja (Persero) Kantor Cabang Jawa Tengah - Priyanti, Oktavina Herdiani; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2015)
Increasingly complex and intense competition in the service industries has forced top managers to seek the most appropriate strategies to win the competition. One of the strategies to achieve success in the service industry,is the applicationof the equity compensation plays an important role in the empowerment of human resources, because in the service industry, human resources potential spearheading the company's success. So far, research on equity compensation is still minimal, for that is the need for research that addresses fairness in compensation as the main topic.Research